Effective gossypol removal from cottonseed meal through optimized solid-state fermentation by Bacillus coagulans - Zhang, Zhenting; Yang, Danlu; Liu, Ling; Chang, Zhangbing; Peng, Nan (Microbial cell factories, 2022)
Cottonseed meal (CSM) is the main by-product of the cottonseed oil extraction process with high protein content, which is an important protein source for feed industry. However, CSM contains free gossypol (FG), a toxic substance that is detrimental to animal health and greatly limits its application. Microbial fermentation is currently considered to be one of the most effective methods to reduce FG and other anti-nutritional factors in CSM. Previously, yeast and bacteria species are used for degradation of FG in CSM, but showing less detoxification efficiency. Bacillus coagulans combines the properties of both lactic acid bacteria and Bacillus, producing both lactic acid and spores, and is considered a potential probiotic. In this study, we aimed to evaluate and optimize the effect of the solid-state fermentation process using a Bacillus coagulans to gossypol removal contained cottonseed meal. 36 B. coagulans strains were isolated and found to have the ability to remove free gossypol. Through the evaluation of strains and optimization of fermentation conditions including fermentation temperature, ratio of material to water, inoculation amount, fermentation time and pH, we have established a solid-state fermentation process using a Bacillus coagulans strain S17 on CSM substrate with 1:1 of the material-to-water ratio, 15% (v/w) seed inoculation, 2% expanded corn flour, 1% bran, and 0.3%-0.8% metal irons at 40 °C for 52 h. After fermentation, the FG content in CSM was reduced from 923.80 to 167.90 mg/kg with 81.83% detoxification efficiency. Meanwhile, the crude protein content in CSM increased from 47.98 to 52.82%, and importantly, the spore concentration of strain S17 reached 1.68 × 10 CFU/g dry material. The study showed that B. coagulans have the potential strong ability to degrade free gossypol through cottonseed meal fermentation. This study presents a feasible process for improving the resource utilization rate and nutritional value of CSM via solid-state fermentation through B. coagulans S17.